INTRODUKSI PDRB RIEL RANTAI NILAI BAGI BPS SURAKARTA DAN SUKOHARJO - Riyardi , Agung; Setiaji, Bambang; Purnomo, Didit; Triyono, Triyono (Universitas Nusantara PGRI Kediri, 2016)
GRDP counting based on chain value method is important to be known by Surakarta’s and Sukoharjo’s stakeholders. The provided data can accompany GRDP counting based on current and constant price methods so that the macro economy of Surakarta and Sukoharjo is described well. The aim of this public serving is to raise the know-how of Surakarta and Sukoharjo Statistics through motivation encouraging, strengthening and sustaining of GRDP chain value method counting. The public service method is an assistancy method by offering discussion, practising and performing a simple ‘animation’ of GRDP counting using chain value method. The result shows that discussion encourages motivation of GRDP counting using chain value method. The result also shows that practicing and performing a simple ‘animation’ of GRDP counting using chain value method do not strengthen and sustain the motivation to raise the know-how. Performing the microsoft powerpoint presentation as a simple ‘animation’ is too simple to sustain the know-how of GRDP counting using value chain method. Therefore, the public serving can motivate the Surakarta and Sukoharjo Statistics, but cannot strengthen and sustain the motivation to raise know-how of GRDP counting using chain value method